PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN MIXUE CILINCING JAKARTA UTARA - Raihan Al Ghifari, Muhammad; Gofur, Abdul (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Judging from the phenomenon that occurred at Mixue Cilincing, North Jakarta, researchers found an increase and decrease in the number of purchases at Mixue Cilincing, North Jakarta which affected their consumer satisfaction. Therefore, this study aims to determine the effect of service quality and product quality on consumer satisfaction at Mixue Cilinicing, North Jakarta. The type of this research is quantitative descriptive. The population in this study were consumers who had made purchases at the Mixue Cilincing, North Jakarta outlet. The sample used was 96 respondents using purposive sampling technique. The analysis tool used was multiple linear regression using IBM SPSS software version 25. The results of the study proved the results of the t-test of the service quality variable (X1) the t-count value> t table (3.532> 1.985) with a significance level of 0.000 <0.05, then Ho was rejected and Ha was accepted. The results of the t-test of the product quality variable (X2) t-value count> t-table (6.060> 1.985) with a significance level of 0.000 <0.05, then Ho is rejected and Ha is accepted. The results of the f-test of the consumer satisfaction variable (Y) f-value count> f-table (202.945> 3.09) with a significance level of 0.000 <0.05, then Ho is rejected and Ha is accepted. So it can be concluded that service quality and product quality simultaneously have a positive and significant effect on consumer satisfaction at Cilincing North Jakarta mixue with a value of 81.4%.